Risk, Course, and Effect of SARS-CoV-2 Infection in Children and Adults with Chronic Inflammatory Bowel Diseases - Angelica Corrias; Gian Mario Cortes; Flaminia Bardanzellu; Alice Melis; Vassilios Fanos; Maria Antonietta Marcialis (MDPI AG, 2021)
Susceptibility and disease course of COVID-19 among patients with inflammatory bowel diseases (IBD) are unclear and epidemiological data on the topic are still limited. There is some concern that patients with immuno-mediated diseases such as IBD, which are frequently treated with immunosuppressive therapies, may have an increased risk of SARS-CoV-2 infection with its related serious adverse outcomes, including intensive care unit (ICU) admission and death. Corticosteroids, immunomodulators, and biologic drugs, which are commonly prescribed to these patients, have been associated with higher rates of severe viral and bacterial infections including influenza and pneumonia. It is not known whether these drugs can be so harmful as to justify their interruption during COVID-19 infection or if, on the contrary, patients with IBD can benefit from them. As shown by recent reports, it cannot be excluded that drugs that suppress the immune system can block the characteristic cytokine storm of severe forms of COVID-19 and consequently reduce mortality. Another cause for concern is the up-regulation of angiotensin converting enzyme-2 (ACE2) receptors that has been noticed in these patients, which could facilitate the entry and replication of SARS-CoV-2. The aim of this narrative review is to clarify the susceptibility of SARS-CoV-2 infection in patients with IBD, the clinical characteristics of patients who contract the infection, and the relationship between the severity of COVID-19 and immunosuppressive treatment.